Konkursy literackie organizowane przez Ministerstwo Kultury i Sztuki w latach 1949−1950 w świetle dokumentów archiwalnych - Budrowska, Kamila (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
This paper focusses on those literary competitions organized by the Ministry of Culture and Arts in the late 1940s and early 1950s. The analysis of the materials from archives offered a chance to tackle the issues: these competitions were one of the many aspects of the Stalinist offensive. Competitions encouraged writers to approach the problems of socialist realism; they forced artists into submission in accordance with Government. The article discusses six competitions. “The third competition on mass song” in which Tadeusz Różewicz, an important writer, took part, was the most curious was one.